From Certification to Consumption: Shariah-Compliant Postmarket Halal Assurance - Thalhah; Hamizar, Arizal; Hunsouw, M. Taib; Roup, Mu'min (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
This study aims to analyze the effectiveness of the regulatory framework in ensuring the halal status of products in Indonesia during the postmarket phase. The primary focus is to evaluate the role of Halal Product Assurance (Jaminan Produk Halal/JPH) supervisors in maintaining compliance with halal standards after certification, including during distribution and sales. The methodology employed is normative legal analysis, utilizing legislative, conceptual, and historical approaches. Research data include key regulations, training materials, and relevant implementation reports. The findings reveal that although Indonesia's halal regulations, such as Law No. 33 of 2014, provide a robust legal foundation, postmarket supervision faces challenges, including limited resources, inter-agency coordination issues, and gaps in implementation. The training of JPH supervisors is identified as a strategic initiative with promising potential to enhance supervision effectiveness, mainly through technology-based programs like Massive Open Online Courses (MOOCs). However, challenges in integrating supervision into the existing regulatory framework remain unresolved. This study underscores the importance of strengthening continuous supervision mechanisms during the postmarket phase to ensure the halal status of products throughout their lifecycle. Thus, postmarket supervision is a technical issue and a moral responsibility aligned with Islamic law principles.